PENGARUH MODAL KERJA DAN LAMA USAHA TERHADAP PENDAPATAN USAHA TANAMAN HIAS DI DESA PETIGA KECAMATAN MARGA KABUPATEN TABANAN - SUDARSANI, NI PUTU (GANEC SWARA, 2020)
This study aims to determine the effect of working capital and business duration variables on ornamental plant business income in Petiga Village, Marga District, Tabanan Regency, with a total sample of 64 respondents. The analytical tool used is multiple linear regression.From the calculation of SPPS 22.00 obtained the calculated F value of 31.088 with a significance of F of 0.000. By using a significance level of 0.05 obtained a F table value of 3.15, then F arithmetic (31.088)> F table (3.15), or a significance of F of 0.000 indicates less than 0.05 so it can be concluded that the two independent variables that is, working capital and business duration jointly influence the amount of ornamental plant business revenue in Petiga Village, Marga District, Tabanan Regency. Partially the working capital variable has a significant effect. While the length of business does not affect the business income of ornamental plants in Petiga Village, Marga District, Tabanan Regency